Collimated dual species oven source and its characterisation via spatially resolved fluorescence spectroscopy. (19th February 2018) - Cooper, N; Da Ros, E; Nute, J; Baldolini, D; Jouve, P; Hackermüller, L; Langer, M
Abstract: We describe the design, construction and characterisation of a collimated, dual-species oven source for generating intense beams of lithium and caesium in UHV environments. Our design produces full beam overlap for the two species. Using an aligned microtube array the FWHM of the output beam is restricted to  ̃75 milliradians, with an estimated axial brightness of 3.6 × 10 14 atoms s −1 sr −1 for Li and 7.4 × 10 15 atoms s −1 sr −1 for Cs. We measure the properties of the output beam using a spatially-resolved fluorescence technique, which allows for the extraction of additional information not accessible without spatial resolution.